1995
DOI: 10.1016/0014-5793(95)01138-5
|View full text |Cite
|
Sign up to set email alerts
|

The transmembrane gradient of the dielectric constant influences the DPH lifetime distribution

Abstract: With the aim of understanding the origin of the variation of DPH decay parameters on the gradient of the dielectric costant, membrane oxidative damage induced by ionizing radiation has been studied [8]. However, in previous work, changes in the gradient of the dielectric constant were postulated on the basis of the changed membrane properties, like membrane lipids phase state, lipid unsaturation, cholesterol content, etc. In our work, we tried to extend these indirect indications to prove directly that lower g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The population of drug molecules in different environments does not change over a time period in the fluorescence lifetime. The other factor is that drug molecules experience an environment of gradient in the dielectric response which occurs on the length scale of the emitting moiety. The time components are composed of shorter components (τ 1 ) around 1.1 ns and longer components (τ 2 ) around 4.2, 3.5, and 3.1 for DMPG, DMPC, and DOTAP liposomes (SI Table 2­(a), 2­(b), and 2­(c)). The longer component is attributed to the liposome-bound DOX.…”
Section: Resultsmentioning
confidence: 99%
“…The population of drug molecules in different environments does not change over a time period in the fluorescence lifetime. The other factor is that drug molecules experience an environment of gradient in the dielectric response which occurs on the length scale of the emitting moiety. The time components are composed of shorter components (τ 1 ) around 1.1 ns and longer components (τ 2 ) around 4.2, 3.5, and 3.1 for DMPG, DMPC, and DOTAP liposomes (SI Table 2­(a), 2­(b), and 2­(c)). The longer component is attributed to the liposome-bound DOX.…”
Section: Resultsmentioning
confidence: 99%
“…The reciprocal of λ max giving the maximal fluorescence intensity of DOX was proportional to the dielectric constant of solvent ( Figure 1D ).The fluorescence spectrum for DVs showed the emission peak at 590 nm in λ max ( Figure 1C ), corresponding to the bulk aqueous environment (ε ~ 75) (estimated by Figure 1D ). Taking into consideration that the dielectric constantmonotonously changes along the vesicle membrane27, it is considered that DOX would be present at the same dielectric environment as the bulk aqueous phase, although some of DOX might be solubilized at membrane region of Span 80 vesicle.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure c, no significant variation in the relative permittivity was observed among the various liposomes tested here, although a slight increase in values was observed in the case of DMPC. It has been reported that there is a gradient of relative permittivity (ε) in the vertical direction across the lipid bilayer membrane, where the ε value of the phosphocholine and glycerol regions can be estimated as approximately 60 and 40, respectively …”
Section: Resultsmentioning
confidence: 99%